Review of the Fund's Income Position for FY2007 and FY200. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The review of income for the year ended April 30, 2007 (FY07) builds on the midyear income review and the February 2007 meeting of the Committee on the Budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Income; Interest Rate; Net Income; PP; SDR; United States